1977
DOI: 10.1017/s0033291700018286
|View full text |Cite
|
Sign up to set email alerts
|

Chronic mania in childhood: case report of a possible association with a radiological picture of cerebellar disease

Abstract: SynopsisThe case-history of a woman with psychiatric symptoms since childhood is reported, the best label for which was that of ‘chronic mania’. Cerebellar atrophy was suspected on radiological grounds. The literature on chronic mania in childhood and on cerebellar damage and mental changes is reviewed and the view is put forward that cerebellar dysfunction may play a part in the production of some psychiatric symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

1982
1982
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
11
0
2
Order By: Relevance
“…Several case reports have identified cerebellar atrophy in patients with mood dysregulation and in patients with bipolar disorder (Cutting 1976;Hamilton et al 1983;Joseph et al 1985;Yadalam et al 1985;Jurjus et al 1994).…”
Section: Since Qualitative Ct Studies Have Suggested Decreased Cerebementioning
confidence: 99%
“…Several case reports have identified cerebellar atrophy in patients with mood dysregulation and in patients with bipolar disorder (Cutting 1976;Hamilton et al 1983;Joseph et al 1985;Yadalam et al 1985;Jurjus et al 1994).…”
Section: Since Qualitative Ct Studies Have Suggested Decreased Cerebementioning
confidence: 99%
“…Indeed, a growing body of evidence points to clinical (514), molecular (1519), neurochemical (2022), structural (2339), and functional (4044) abnormalities of the cerebellum in BP. The cerebellum is reciprocally connected to higher-level association areas in prefrontal (45) and posterior parietal (46) cortices and limbic regions in medial temporal lobe (4749), and cerebellar dysfunction may mirror or contribute to well-established dysfunctions of these higher-level association areas in BP.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, empirical and theoretical evidence have indicated that the cerebellum plays a significant role in psychological functions as well, including modulation of perceptual, cognitive, and affective functions [8], [9], [10], [11], [12], which is believed to occur via its modulation of the anterior limbic network [1], [13], [14], [15]. Structural imaging studies indicate cerebellar abnormalities, in particular, cerebellar atrophy in BD [13], [16], [17], [18], [19], [20], [21], [22]. Neurochemical alterations have also been reported [23], [24], [25], [26].…”
Section: Introductionmentioning
confidence: 99%